Anti Inflammatory Studies of Barringtonia acutangula (Linn) Fruits on Wistar Rats. - Avula Muralidhar; C Sainath Reddy; A. Someswara Yadav; J Kedareeswari; B Sankaraiah; B Vijayakumar; G. Varalakshmi (International Journal of Phytomedicine, 2013)
The study aims to evaluate the anti inflammatory activity of Barringtonia acutangula (Linn) fruit extracts in wistar rats. In this study fruits of Barringtonia acutangula were extracted with ethanol and purified water, these extracts were subjected to preliminary phytochemical analysis to identify their phytoconstituents. The ethanol and aqueous extracts were evaluated in vivo by using acute inflammatory models like; carrageenan induced paw oedema and chronic models like; cotton-pellet induced granuloma and carrageenan induced air-pouch model in rats. The biochemical parameters like reduced glutathione (GSH), lipid peroxidation and catalase were also estimated as supportive studies. Acute toxicity studies were performed initially in order to ascertain the safety of ethanol and aqueous extracts. The ethanol extract reduced the inflammation more significantly than the aqueous extract in the carrageenan-induced rat paw oedema, cotton-pellet induced granuloma and carrageenan induced air-pouch model in rats. The phytochemical investigation of the ethanol fruit extract showed the presence of phytosterols, glycosides, flavonoids, alkaloids and carbohydrates. From the present study the ethanolic fruit extract of Barringtonia acutangula exhibited the anti-inflammatory effect by augmenting antioxidant defense system in the inflammation bearing rat, which is largely attributable to the additive or synergistic effect of its constituents.